SUSTAINABLE ACHIEVEMENT SPORTS DEVELOPMENT PROGRAM IN DKI JAKARTA PROVINCE (Evaluation Study in Swimming) - PRANAJAYA, IKROOM; Abdul sukur; Aan Wasan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
ABSTRACT Competitive performance sports require achieving maximum performance for those who pursue it either individually, in groups or as teams. This means that achievement in sports is the final goal that must be achieved in a sports activity. To achieve this, one way that can be done is through coaching efforts through the implementation of programmed training in a systematic, directed and continuous manner. DKI Jakarta Province implements the Sustainable Achievement Sports Development Program which adapts the long-term development model from Balyi. This research aims to evaluate the DKI Jakarta Province Sustainable Sports Achievement Development Program, especially in swimming in 2023. This research uses the CIPP evaluation model from Stufflebeam including Context, Input, Process and Product. This research was carried out from February to August 2024 at the Sustainable Sports Achievement Development Program at the DKI Jakarta Provincial Youth and Sports Service. Keywords: Evaluation, Context, Input, Process and Product, Sustainable Performance Sports Development Program, Swimming